Pendampingan Penulisan Pantun sebagai Upaya Pelestarian Warisan Budaya di SMK Masehi Berastagi - Ernawati Br Barus; Harry Dito Meliala; Vera Charoline Br Barus (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Language is known as a tool for interaction or communication that people use every day in various contexts, including education, economy, travel, and religion. Language skills include four components: speaking, listening, reading, and writing. From the learning outcomes are still low with 6 students failing, researchers need to make improvements to learning. The purpose of this improvement is so that researchers can improve weaknesses in the next. Based on the results obtained by researchers in implementing research at SMA Bersama Berastagi both through assignments, Student Worksheets (LKS) and Based on the results of the exam, students' ability to write drama scripts has increased. This is evidenced by students having mastered the skills of writing drama scripts.